Hydrodynamic dispersion of pressure-induced and electroosmotic flow in porous glasses probed by Nuclear Magnetic Resonance - Li, Yujie; Farrherr, German; Kimmich, Rainer (Diffusion Fundamentals, 2007)
Fluid transport by flow in random porous media is subject to hydrodynamic dispersion. In a series of pulsed field-gradient NMR experiments, we have compared flow induced by pressure gradients on the one hand and by electroosmosis on the other. The media were porous glasses with pore dimensions from 1 to 100 μm. With increasing flow rates, a crossover from subdiffusive to superdiffusive mean-squared displacement laws was observed in both cases. This demonstrates the competition between molecular diffusion and convection, and is a typical example of anomalous transport.